Size-dependent microstructure evolution and formation mechanisms during the gas atomization process of FGH4113A Ni-based superalloy powder. (March 2023) - Pan, Hao; Zhu, Lihua; Cheng, Junyi; Xiao, Lei; Ji, Hongjun
Abstract: A novel microstructure evolution mechanism is proposed to optimize the preparation process of superalloy powders. This study focuses on the solidification segregation, as well as the correspondence between the powder sizes and the microstructure evolution mechanism of Ni-based superalloy fine powders. The quantitative analysis was systematically examined using thermodynamic analysis. The results indicated that dendrites and cellular microstructures formed on the surface and interior of the powders, but their key distribution characteristics were highly related to both the powder size and ultra-fine satellite particles that adhered to its surface. The number of ultra-fine satellite particles, outgrowth index, spacing between the secondary dendrite arms increased with the increasing powder size, exhibiting an ideal linear relationship. In particular, when the powder size was small, the length of the internal primary dendrite arms increased as the powder particle size increased, but interestingly, remained at approximately 30 μm when the particle size exceeded 45 μm. Finally, a model for the microstructural evolution mechanism of the surface and interior of alloy powders ≤100 μm was developed, which lays the theoretical foundation for the preparation of superalloy powders. Highlights: Microstructure was related with powder size and the ultra-fine satellite particles. The η, η outgrowth, and d exhibited a linear increasing trend with the powder size. The d primary increased initially but remained 30 μm when the sizes exceeded 45 μm.